Última lembrança: uma investigação sobre a produção da fotografia mortuária no sertão baiano - Santana, Graziela Gomes (2025)
As a visual witness to the past and with its propensity for immortality, photography allows for the recording of a kind of biography of ordinary people, spanning all phases and various moments of life. It serves as a valuable document with an emotional dimension. Among the various types of photographs, post mortem portraits taken during the wake or burial stand out. This study aims to investigate and discuss the presence, production, and consumption of mortuary photographs as memory objects created in the 20th century and found in the hinterlands of Bahia, specifically in the microregion of Jacobina and the city of Senhor do Bonfim. The research consists of a serial study through the mapping and analysis of post mortem photographs, highlighting patterns and variations in the representations of the deceased and their relationship with the social context of these iconographic artifacts. Thus, photography, especially mortuary photography, emerges as a fundamental tool in the preservation of memory, enabling fragments of personal and collective history to be perpetuated. In the Bahian hinterlands, this custom reveals unique ways of experiencing mourning and reinterpreting absence, functioning as a bridge between the past and the present.